A review of animal and human health concerns during capture-release, handling and tagging of odontocetes - Norman , S. A.; Hobbs , R. C.; Foster, J.; Schroeder, J. P.; Townsend, F. I. (J. Cetacean Res. Manage., 2023)
The capture-release of odontocetes allows for tag deployment which provides an opportunity to study behaviour and habitat use by free-ranging animals, as well as clinical assessment of the animal and tissue collection. This review recognises those elements that are common to most capture and tagging projects, identifies collective knowledge of animal and human health concerns during handling of odontocetes and provides guidelines for safer handling techniques. Handling during tagging projects can involve chase, capture, restraint, manipulation, tag application, often removal from the water and release at the capture site. The risk of injury during capture will be reduced by using experienced personnel, adequate technical support and proper equipment. For the duration of the handling process, the animal’s stimulus response should be monitored as well as its cardiovascular and respiratory function. Stress response of the odontocete is monitored by behavioural assessments, physiological monitoring and/or blood sampling. Possible complications from tag placement may include infection at the implant site leading to tag failure, behavioural alterations in response to tag placement and tag rejection. During handling of an odontocete, there is the potential for disease transmission between humans and the animal. Exposure to diseases is minimised by wearing protective clothing and gear and exercising caution when working around the animal’s blowhole.